(3ebOeI aj GdJLGQI GdGdcJQhfjI GdYQHjI (B:s (3TQM bGfhf GdeHGOdGJ h GdJLGQI GdGdcJQhfjI GdJhfSjI (B/s - (3MLGRj, YHO GdaJGM Hjhejs ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2004)
(3eONd Gdi GdJLGQI GdGjdjcJQhfjI aj OhdI GdGeGQGJ GdYQHjI GdeJMOI h GdGMcGe GdYGeI ddJLGQI GdGdjcJQhfjI dOi GeGQI OHj eY eJWdHGJ GdeYGedGJ GdGjdjcJQhfjI , GdSLdGJ h GdJhbYGJ GdGjdjcJQhfjI GdeMejI h GdGMcGe GdeJUdI HGdTgGOGJ h NOeGJ GdJUOjb h CNjQG GdGSJNOGeGdMchej h GdJhbYGJ GdGdcJQhfjI (B.s
Keywords: (3GdJLGQIs; (3GdJLGQI GdGdcJQhfjIs; (3GdJLGQI GdYQHjI(B- (3JhfSs